CHOLECYSTECTOMY FOR GALL STONES IN 26 MONTHS OLD CHILD - Zeb, Junaid; Asad, Shawana; Khattak, Irfanud Din; Hussain, Mubashir (Journal of Ayub Medical College Abbottabad, 2017)
Cholelithiasis is a major cause of morbidity worldwide. The incidence of gall stone in children in Pakistan has not been sufficiently studied and is increasingly being detected: the reason may be a true rise in the incidence or an improvement in diagnosis due to liberal use of diagnostic facilities and thus the increased opportunity to detect disease. A healthy 2 years and 2 months old male child presented to outpatient with history of recurrent attacks of pain abdomen and anorexia. Ultrasonography showed a 0.6 mm stone, inflammation and pericholecystic fluid. Open cholecystectomy was performed under general anaesthesia. A distended gall bladder with multiple very small calculi was removed. Post-operative stay was uneventful and patient was allowed oral feeds after 24 hours. Keywords: Acute Cholecytitis; Paediatric Cholelithiasis; Cholecystectomy